2021
DOI: 10.3934/geosci.2021027
|View full text |Cite
|
Sign up to set email alerts
|

Artificial neural network based PERSIANN data sets in evaluation of hydrologic utility of precipitation estimations in a tropical watershed of Sri Lanka

Abstract: <abstract> <p>The developments of satellite technologies and remote sensing (RS) have provided a way forward with potential for tremendous progress in estimating precipitation in many regions of the world. These products are especially useful in developing countries and regions, where ground-based rain gauge (RG) networks are either sparse or do not exist. In the present study the hydrologic utility of three satellite-based precipitation products (SbPPs) namely, Precipitation Estimation from Rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Model. An artificial neural network (ANN) uses multiple neurons to connect with each other, simulates the neural information processing mode of the human brain through a neural network, and realizes nonlinear transformation and parallel processing of information [15]. A neural network is used to simplify, abstract, and simulate human brain thinking.…”
Section: Deep Learning Neural Networkmentioning
confidence: 99%
“…Model. An artificial neural network (ANN) uses multiple neurons to connect with each other, simulates the neural information processing mode of the human brain through a neural network, and realizes nonlinear transformation and parallel processing of information [15]. A neural network is used to simplify, abstract, and simulate human brain thinking.…”
Section: Deep Learning Neural Networkmentioning
confidence: 99%
“…A previous study was carried out for the Mundeni Aru Basin, Sri Lanka, to evaluate the applicability of SRPs in flood hazard mapping [28]. Two other studies attempted to determine the accuracy of SRPs in streamflow simulation for the Seethawaka watershed, Sri Lanka, using a hydrological model [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…The results of the study in the Upper Nan demonstrated that the PERSIANN product significantly underestimates observed streamflow. In addition, Gunathilake et al [64,65] showcased similar cases for the PERSIANN group of products over the Seethawaka watershed, a sub-watershed of the Kelani watershed of Sri Lanka.…”
Section: Evaluation Of Streamflow Simulation Capacity Of Different Precipitation Productsmentioning
confidence: 82%